2021
DOI: 10.3390/jcm10132799
|View full text |Cite
|
Sign up to set email alerts
|

Diagonal Earlobe Crease (Frank’s Sign) for Diagnosis of Coronary Artery Disease: A Systematic Review of Diagnostic Test Accuracy Studies

Abstract: Coronary artery disease is a global challenge for healthcare systems. Early diagnosis is a key issue to improve quality of life and reduce morbidity and mortality. Diagonal earlobe crease, a wrinkle extending obliquely across the earlobe, was linked by many authors to various atherosclerotic diseases. This systematic review aimed at summarizing the diagnostic accuracy of diagonal earlobe crease for diagnosis of chronic and acute coronary syndromes in adults. Cochrane’s recommendations for systematic reviews of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…EC occurs via vascular endothelial dysfunction, which is also associated with the development of coronary vascular disease and other conditions [ 14 , 18 ]. Furthermore, EC associated with atherosclerosis may also be induced by skin aging, collagen degeneration, and telomere shortening [ 19 , 20 , 21 , 22 ]. The EC lesion induced by these consequences ultimately alters the shape of the ear, through the progression of ischemia-induced fibrosis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…EC occurs via vascular endothelial dysfunction, which is also associated with the development of coronary vascular disease and other conditions [ 14 , 18 ]. Furthermore, EC associated with atherosclerosis may also be induced by skin aging, collagen degeneration, and telomere shortening [ 19 , 20 , 21 , 22 ]. The EC lesion induced by these consequences ultimately alters the shape of the ear, through the progression of ischemia-induced fibrosis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“… 11 Furthermore, a recent systematic review showed that the diagnostic accuracy of diagonal earlobe crease for detecting chronic coronary syndromes is insufficient. 12 Additionally, the Fremantle Diabetes Study assessed the clinical usefulness of FS as a sign of coronary artery disease or retinopathy in type 2 diabetes. 13 This study found that FS was not a significant independent predictor of either coronary artery disease or retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, an observational study found no significant association between FS and abnormal ankle‐branchial index 11 . Furthermore, a recent systematic review showed that the diagnostic accuracy of diagonal earlobe crease for detecting chronic coronary syndromes is insufficient 12 . Additionally, the Fremantle Diabetes Study assessed the clinical usefulness of FS as a sign of coronary artery disease or retinopathy in type 2 diabetes 13 .…”
Section: Discussionmentioning
confidence: 99%
“… 41 In the meantime, there are several systematic reviews disproving such association. 42 , 43 There is also emerging research linking ELC to the mechanical traction secondary to visceral obesity of the face. 44 Furthermore, congenital earlobe creases were notes in neonates with Beckwith-Wiedemann syndrome.…”
Section: Discussionmentioning
confidence: 99%